Predictors of orphan drug approval in the European Union - Heemstra, Harald E. (Springer-Verlag, 2008)
OBJECTIVE: To encourage the development of drugs for rare diseases, orphan drug legislation has been introduced in the USA (1983) and in the EU (2000). Recent literature discusses factors that may influence the development of new orphan medicinal products in the EU. This study aims to identify predictors for successful marketing authorisation of potential orphan drugs in the EU. METHODS: A comparison between randomly selected authorised and a matched sample of not-yet-authorised orphan drug designations has been performed. Determinants in the study included characteristics of the indication, of the product and of the sponsor. Data were collected from the public domain only. RESULTS: Orphan drug approval was strongly associated with previous experience of the sponsor in obtaining approval for another orphan drug (OR = 17.3, 95% CI = 5.6–53.1). Furthermore, existing synthetic entities compared to biotechnology products tended to have a higher likelihood of reaching approval status (OR = 3.9, 95% CI = 0.9–16.6). CONCLUSION: This study showed that experience of a company in developing orphan drugs is an important predictor for subsequent authorisation of other orphan drugs. The same applies for existing (synthetic) molecules, for which much knowledge is available. Further research should be directed towards studying the quality of the clinical development program of those designated orphan medicinal products not reaching approval status.